Fundamentals of wireless communication - Tse, David; Viswanath, Pramod (Cambridge University Press, 2005)
The past decade has seen many advances in physical layer wireless communication theory and their implementation in wireless systems. This text presents a unified view of the fundamentals of wireless communication for graduate students and practising engineers.